An eternal lei - Hirahara, Naomi, 1962- (Hirahara, Naomi, 1962- Leilani Santiago Hawai'i mystery, 2022)
"It's the middle of the pandemic and Hawai'i has been virtually closed to tourists. So when Leilani Santiago and her young sisters save a mysterious woman wearing a lei from drowning in Waimea Bay in Kaua'i questions abound: who is she and where did she come from? The lei, which is made of mokihana berries, the official flower of Kaua'i, is traced back to Leilani's best friend, the very pregnant Courtney Kahuakai, and her family's flower business. While the woman is in a medically induced coma in a local hospital, Leilani languishes as her shave ice shack is temporarily shuttered due to the pandemic. Leilani becomes obsessed with the woman and even breaks into her Airbnb to discover her identity. She finds that the woman, a travel agent who has a Japanese passport, has information about a local attorney on the island, Garvin Washburne. When Washburne shoots and kills a hospital nurse who, armed with a machete, had trespassed into the attorney's home, Leilani is further drawn into this mystery. As residents protest the reopening of tourism, do Garvin and the travel agent from Japan represent the opposition? Soon the future of Leilani's family member is threatened and Leilani realizes the serious repercussions of her amateur investigation. The survival of Leilani, her family and friends will depend on her sense of ingenuity and the strength of her island community"--